Measurement of velocities of copper nanoparticles exiting a gas aggregation source. (August 2022) - Solař, Pavel; Škorvánková, Kateřina; Kuzminova, Anna; Kousal, Jaroslav; Kylián, Ondřej
Abstract: Gas aggregation sources have become a valuable tool for the effective production of nanoparticles and nanoparticle films. In some cases (e.g. during in-flight coating of nanoparticles or interaction between nanoparticles and substrate), the critical parameter that influences the applicability of these sources and properties of fabricated nanomaterials is the velocity of produced nanoparticles. Naturally, to control the speed of nanoparticles, it is crucial to determine how it is influenced by process parameters. A mechanical time-of-flight filter has been used to measure the velocities of nanoparticles exiting a magnetron-based gas aggregation source. Nanoparticle velocities have been investigated for various deposition conditions, including aggregation chamber pressure from 20 to 100 Pa, magnetron current from 100 to 500 mA and deposition chamber pressure from 0.015 to 2.5 Pa. Nanoparticles may be accelerated in the area around the exit orifice and decelerated by the background gas in the deposition chamber. This allows tailoring the nanoparticle velocity in the range from 10 m s −1 up to over 100 m s −1 . Furthermore, the dependence of the velocity of nanoparticles on their size was found to obey a simple power law. Therefore, the filter may be used not only as a velocity filter but also as a mass filter. Highlights: High resolution nanoparticle velocity measurement outside of gas aggregation source. Measurement of velocity of nanoparticles including neutral ones. Mass filtration of nanoparticles including neutral ones. Nanoparticles deceleration by background gas.